In the family way: an exploration of family business resilience. Issue 1 (19th September 2019) - Beech, Nick; Devins, David; Gold, Jeff; Beech, Susan
Abstract : Purpose: This paper aims to explore the concept of resilience set within a family business context and considers how familiness and the nature of noneconomic factors, such as relationship dynamics influence performance. This paper provides new insights into the nature and impact of familiness as a mediating device, uncovering the potential for reframing resilience theory and practice. Design/methodology/approach: The paper draws on a review of the extant literature in the areas of resilience and familiness as a means of developing a deeper understanding of the social-ecological system of the family firm. Findings: The study reveals family business as a complex interrelationship between complimentary social-ecological systems. It highlights the complexity of family business and the challenges of the relational nature of familiness and how this presents additional layers of complexity in the decision making process and implementation. Research limitations/implications: The paper draws on literature that is dominated by western culture and may partially or not at all reflect the issues associated with organisational resilience in family firms with such backgrounds and their culturally bound social-ecological systems. Originality/value: The paper seeks to fill a knowledge gap by exploring the key elements of organisational resilience in the context of familiness. The work calls for further research into the nature of familiness connections mediating the nature of family relational dynamics. It further provides a framework indicating how these elements can shape and subvert day-to-day management events, raising implications for theory and practice and calls for deeper empirical research to be undertaken.